Avaliação da resistência à corrosão intergranular do aço inoxidável austenítico ASTM F138 - Alberto, Caique Augusto Teixeira (Universidade Federal de São Carlos, 2023)
ASTM F138 austenitic stainless steel is used in the form of plates and screws as permanent surgical implants. Due to its critical application, when compared to AISI 316, this steel contains a processing route with Electro Slag Remelting (ESR), a reduction in the impurities content such as sulfur and phosphorus, and a reduction in the carbon content (< 0.03 weight %). This last change aims to increase the intergranular corrosion resistance of ASTM F138 by reducing the precipitation kinetics of chromium-rich carbides, especially M23C6, which are known for the sensitization phenomena in stainless steels. Nevertheless, studies on the susceptibility to intergranular corrosion must be carried out to ensure the absence of this phase that could cause premature failure of the material under service conditions. In this study, ASTM F138 steel samples were aged for up to 24 h at 675 °C. Oxalic acid solution test according to ASTM A262 method A (A262/A) associated with the use of the Double-Loop Electrochemical Potentiokinetic Reactivation technique (DL-EPR) were performed. The sweep range, one of the control parameters of the DL-EPR test, was adjusted to allow the evaluation of ASTM F138 steel. A262/A test results showed a change in microstructural morphology from step, to dual, and, finally, ditches with increasing aging time. In addition, DL-EPR test showed absence of reactivation for samples with step morphology, but presence of reactivation for samples with dual and ditches. The correlation and agreement between A262/A and DL-EPR tests after the sweep range adjustment allowed to evaluate the susceptibility to intergranular corrosion of low carbon austenitic stainless steels like ASTM F138.
Evaluation of intergranular corrosion resistance of the ASTM F138 austenitic stainless steel
Keywords: ASTM F138; ASTM A262/A; DL-EPR; Corrosão intergranular; Intergranular corrosion; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA